2014
DOI: 10.5455/ijmsph.2014.210220143
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive study of the socio-demographic determinants influencing adolescent pregnancy in Shimoga Town, Karnataka

Abstract: Background: Young age at pregnancy carries significant risk for the mother and baby, adding to the burden of maternal and child mortality. Aims & Objective: (1) To study the socio-demographic factors influencing adolescent pregnancy; (2) To take an account of the awareness among women about the right age for child-bearing. Materials and Methods: A hospital-based study was undertaken during September to December 2013 among mothers attending the antenatal clinic, in Mc Gann Hospital, Shimoga. The study group com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…A significant lack of awareness about family planning among married adolescent girls was highlighted in two studies. In contrast to these studies [ 47 , 50 ], Only one article reported that most married adolescents were aware of contraception [ 49 ]. Experiences and understanding related to pregnancy among adolescents Sexual intercourse with a lack of understanding of contraception, family planning, sex, and abortion can lead to pregnancy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant lack of awareness about family planning among married adolescent girls was highlighted in two studies. In contrast to these studies [ 47 , 50 ], Only one article reported that most married adolescents were aware of contraception [ 49 ]. Experiences and understanding related to pregnancy among adolescents Sexual intercourse with a lack of understanding of contraception, family planning, sex, and abortion can lead to pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…Five articles explained the understanding of the use of contraception to prevent unwanted pregnancy [ 14 , 41 , 43 45 ]. Lack of awareness about contraceptive methods and reproductive health was discussed in eight articles [ 44 , 49 , 55 , 56 , 58 , 61 , 63 ]. A study by Ahuja et al (2009) explained consultation after the failure of contraception among adolescents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation